2011
DOI: 10.5007/1980-0037.2009v11n3p326
|View full text |Cite
|
Sign up to set email alerts
|

Magnitudes de impacto e cinemática dos membros inferiores no arremesso em suspensão no handebol

Abstract: Resumo-O objetivo deste estudo foi investigar as características cinemáticas e de impacto na aterrissagem do arremesso em suspensão dos atletas amadores de handebol. Participaram deste estudo nove atletas universitários do sexo masculino. Foi utilizado um acelerômetro triaxial para identificar as magnitudes de impacto nos membros inferiores e o sistema de reconstrução tridimensional de movimento DMAS 5.0® para analisar os ângulos de flexão do joelho e quadril na aterrissagem do arremesso. Os dados da cinemátic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…In order to obtain signals from the accelerometer we used the model MMA7340 of Freescale semiconductors. This system is formed by microelectronics mechanisms (MEMS), which explore the mechanical proprieties of silicone to create movable structures and to detect distinct movement directions [18] , [19] , [20] . The capture of movements was conducted in actual time system with the interaction of EEG software signal acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…In order to obtain signals from the accelerometer we used the model MMA7340 of Freescale semiconductors. This system is formed by microelectronics mechanisms (MEMS), which explore the mechanical proprieties of silicone to create movable structures and to detect distinct movement directions [18] , [19] , [20] . The capture of movements was conducted in actual time system with the interaction of EEG software signal acquisition.…”
Section: Methodsmentioning
confidence: 99%
“…Em atletas praticantes de basquetebol e voleibol, ao realizar os treinos e partidas de competição, estão sempre sujeitos a lesões devido a biomecânica dos saltos para os arremessos e as defesas; que na verdade são uma sequência de movimentos repetitivos e recorrentes que levam ao acometimento de lesões; principalmente nos movimentos de saltos durante aterrissagem que podem ocasionar lesões nos joelhos e tornozelos, regiões que sofrem mais com os impactos (PIUCCO et al, 2007;SANTOS et al, 2009;SANTOS et al, 2007).…”
Section: O Efeito Do Impacto Repetitivo Com O Solo Em Práticas Esport...unclassified
“…However, it is reported that when handball players perform a jump from the dominant leg, the jumping distance was approximately 5% larger than executing the jump with the non-dominant leg [44]. This can be attributed to the fact that the execution of the jump shot subjects the contralateral to the throwing arm leg to considerable mechanical loading [45][46][47][48]. Furthermore, long-term submission to systematic training results in sportspecific adaptations in strength and conditioning features [49], as well as to the factors that define handball performance [44].…”
Section: Introductionmentioning
confidence: 99%